THE IMPACT OF PRENATAL EXPOSURE TO PARACETAMOL ON THE OCCURRENCE OF NEURODEVELOPMENTAL DISORDERS IN CHILDHOOD: A LITERATURE REVIEW - Aleksandra Miśta; Paweł Harbut; Aleksander Białoń; Dominika Walczak; Weronika Ewa Nowak; Adrian Kruk; Katarzyna Jakubowska; Aleksandra Dorosz; Igor Gawłowski; Lidia Jurczenko (International Journal of Innovative Technologies in Social Science, 2025)
Background: In recent years, several large cohort studies have drawn attention to a possible association between maternal paracetamol use during pregnancy and the occurrence of neurodevelopmental disorders. Given the complex etiology of these conditions and the fact that acetaminophen is considered the only safe analgesic and antipyretic during pregnancy, these publications have generated both concern and controversy.Methods: This paper is based on studies published in PubMed. The reviewed literature includes publications from 2000 to 2025, primarily involving large cohorts (typically at least 100 participants) and accounting for potential confounding factors. The search terms used were “paracetamol,” “acetaminophen,” “neurodevelopmental disorders,” “autism,” and “ADHD.” Based on these criteria, 41 articles were selected for analysis.Results: Cohort studies demonstrated a slight increase in the risk of neurodevelopmental disorders associated with prenatal acetaminophen exposure. However, a causal relationship has not been established.Conclusions: Paracetamol may have an adverse effect on fetal nervous system development; therefore, its use during pregnancy should be limited to cases with clear medical indication and in accordance with the product’s prescribing information.